Síntese verde e caracterização de nanopartículas de ouro utilizando o extrato da Cordia Erbenacea - Sores Sena, Felipe (2023)
In this study, the biosynthesis of gold nanoparticles will be carried out using different parts of the Cordia Verbenacea plant, which is better known as Erva Baleeira, is a plant native to Brazil, found throughout Latin America, a shrubby plant used in traditional medicine as an anti-inflammatory, to relieve muscle pain, arthritis and other rheumatic conditions. To produce gold nanoparticles (AuNPs), a solution containing tetrachloroauric acid (III) (HAuCl4.3H2O) with a concentration of 1.0x10-3 M was prepared. Furthermore, an infusion was prepared using 5 g of different parts of the Cordia Verbenacea plant in 100 mL of distilled water, heated to 80°C and left to rest for 15 minutes. The filtered infusion solution will be used as a reducing and stabilizing agent in the synthesis of (AuNPs). For the AuNPs formation reaction, 1 mL of the infusion was added to 20 mL of the HAuCl4.3H2O solution under constant stirring for 5 minutes, subsequently heated to 80 °C. After heating, the color change of the solution from yellow to dark violet, showing a possible formation of anoparticles, to confirm the formation of AuNPs, characterization was carried out by UV-vis spectroscopy where the AuNPs showed a strong absorption band in the visible region between 531 nm. Fourier transform infrared spectroscopy (FT-IR) analysis suggests that the biomolecules present in the extract were responsible for the reduction and stabilization of AuNPs. Topographic analysis carried out by atomic force microscopy (AFM) indicated a spherical shape, with an average size of 78 nm. Based on the potential of green synthesis of gold nanoparticles, which is a simple method, Cordia Verbenacea aqueous extract is an alternative for the biosynthesis of (AuNPs) with promising biomedical applications.